Direct bone morphogenetic protein 2 and Indian hedgehog gene transfer for articular cartilage repair using bone marrow coagulates. Issue 3 (March 2015) - Sieker, J.T.; Kunz, M.; Weißenberger, M.; Gilbert, F.; Frey, S.; Rudert, M.; Steinert, A.F.
Summary: Objective: Bone morphogenetic protein 2 (BMP-2, encoded by BMP2 ) and Indian hedgehog protein (IHH, encoded by IHH ) are well known regulators of chondrogenesis and chondrogenic hypertrophy. Despite being a potent chondrogenic factor BMP-2 was observed to induce chondrocyte hypertrophy in osteoarthritis (OA), growth plate cartilage and adult mesenchymal stem cells (MSCs). IHH might induce chondrogenic differentiation through different intracellular signalling pathways without inducing subsequent chondrocyte hypertrophy. The primary objective of this study is to test the efficacy of direct BMP2 and IHH gene delivery via bone marrow coagulates to influence histological repair cartilage quality in vivo . Method: Vector-laden autologous bone marrow coagulates with 10 11 adenoviral vector particles encoding BMP2, IHH or the Green fluorescent protein ( GFP ) were delivered to 3.2 mm osteochondral defects in the trochlea of rabbit knees. After 13 weeks the histological repair cartilage quality was assessed using the ICRS II scoring system and the type II collagen positive area. Results: IHH treatment resulted in superior histological repair cartilage quality than GFP controls in all of the assessed parameters (with P < 0.05 in five of 14 assessed parameters). Results of BMP2 treatment varied substantially, including severe intralesional bone formation in two of six joints after 13 weeks. Conclusion: IHH gene transfer is effective to improve repair cartilage quality in vivo, whereas BMP2 treatment, carried the risk intralesional bone formation. Therefore IHH protein can be considered as an attractive alternative candidate growth factor for further preclinical research and development towards improved treatments for articular cartilage defects.